An in vitro study of the antifungal activity of Trichoderma virens 7b and a profile of its non-polar antifungal components released against Ganoderma boninense - Lee, Pei Lee Angel; Yusof, Mohd Termizi; Ismail, Intan Safinar; Tay, Bonnie Yen Ping; Mohamed Azni, Intan Nur Ainni; Kamarudin, Norman Hj; Sundram, Shamala (Springer Verlag, 2016)
Ganoderma boninense is the causal agent of a devastating disease affecting oil palm in Southeast Asian countries. Basal stem rot (BSR) disease slowly rots the base of palms, which radically reduces productive lifespan of this lucrative crop. Previous reports have indicated the successful use of Trichoderma as biological control agent (BCA) against G. boninense and isolate T. virens 7b was selected based on its initial screening. This study attempts to decipher the mechanisms responsible for the inhibition of G. boninense by identifying and characterizing the chemical compounds as well as the physical mechanisms by T. virens 7b. Hexane extract of the isolate gave 62.60% ± 6.41 inhibition against G. boninense and observation under scanning electron microscope (SEM) detected severe mycelial deformation of the pathogen at the region of inhibition. Similar mycelia deformation of G. boninense was observed with a fungicide treatment, Benlate® indicating comparable fungicidal effect by T. virens 7b. Fraction 4 and 5 of hexane active fractions through preparative thin layer chromatography (P-TLC) was identified giving the best inhibition of the pathogen. These fractions comprised of ketones, alcohols, aldehydes, lactones, sesquiterpenes, monoterpenes, sulphides, and free fatty acids profiled through gas chromatography mass spectrometry detector (GC/MSD). A novel antifungal compound discovery of phenylethyl alcohol (PEA) by T. virens 7b is reported through this study. T. virens 7b also proved to be an active siderophore producer through chrome azurol S (CAS) agar assay. The study demonstrated the possible mechanisms involved and responsible in the successful inhibition of G. boninense.